2017
DOI: 10.1186/s13019-017-0640-2
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial myxoma complicated with multi-system embolization

Abstract: BackgroundAtrial myxoma accounts for approximately 50% of all cardiac tumors. The majority of myxomas are located in the left atrium and present variable clinical manifestation.Case presentationA young man was transferred to our hospital with sudden onset of resting pain, pallor and numb in right leg. An atrial mobile mass was detected by transthoracic echocardiography. Anticoagulant and antithrombotic therapy were administered, a timely surgery was performed and the mass was confirmed as a myxoma. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…Most often, less obvious cardiac symptoms are discovered only after an embolism. [ 5 ] Therefore, cardiac myxomas are often misdiagnosed in the pediatric population. In the 18 previously reported pediatric cases plus our own, 10 children presented with cerebral ischemic stroke prior to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, less obvious cardiac symptoms are discovered only after an embolism. [ 5 ] Therefore, cardiac myxomas are often misdiagnosed in the pediatric population. In the 18 previously reported pediatric cases plus our own, 10 children presented with cerebral ischemic stroke prior to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Henceforth, this report puts emphasis on the fact that AM, though rare, should be considered as a source of embolism in patients presenting with acute limb ischemia. A case series study published in the year 2017 found that 4 out of 46 cases of left AM experienced multisystem embolization [ 15 ]. Common causes of embolism must also be excluded, including COVID-19 viral infection which is known to cause a hypercoagulable state [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While left atrial myxomas are more common than the right-sided counterpart and give suspicion for their presence via their distant manifestations despite other risk factors for distal embolic phenomenon, right atrial myxomas still need attention especially in the setting of PE without any or significant risk factors. 59 Furthermore, evidence of myocardial injury suggested an alternative diagnosis was reasonable. However, there seemed to be a disconnect between the patient’s clinical evaluation and her radiographic thrombus burden.…”
Section: Discussionmentioning
confidence: 99%